Bcl6 is a subset defining transcription factor of Lymphoid Tissue inducer-like ILC3 - Tachó-Piñot, Roser (Cell Rep, 2023)
Innate lymphoid cells (ILCs) are tissue-resident effector cells with roles in tissue homeostasis, protective immunity, and inflammatory disease. Group 3 ILCs (ILC3) are classically defined by the master transcription factor RORγt. However, ILC3 can be further subdivided into subsets that share type 3 effector modules that exhibit significant ontological, transcriptional, phenotypic, and functional heterogeneity. Notably lymphoid tissue inducer (LTi)-like ILC3 mediate effector functions not typically associated with other RORγt-expressing lymphocytes, suggesting additional transcription factors contribute to dictate ILC3 subset phenotypes. Here we identify Bcl6 as a subset-defining transcription factor of LTi-like ILC3 in mice and humans. Deletion of Bcl6 results in dysregulation of the LTi-like ILC3 transcriptional program and markedly enhances expression of IL-17A and IL-17F in LTi-like ILC3, in a manner in part dependent upon the commensal microbiota - and associated with worsened inflammation in a model of colitis. Together these findings redefine our understanding of ILC3 subset biology.